Regulation of Market of Alcohol Beverage Import as Factor of Providing National Security in Russia - O V. Prokhorova (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article studied market of alcohol beverage in Russia, it showed the level of consumption and poisoning by alcohol, identified the most ‘alcohol drinking’ regions and the structure of consumption, researched the level of illegal production and presence of ethyl alcohol, alcohol and alcohol-containing products in circulation. The level of alcohol beverage production in Russia was analyzed by types and features and structure of alcohol beverage import to our country was analyzed by types and countries. Specificity of regulating market of alcohol beverage import to Russia was investigated and key trends of customs control were demonstrated as a way to prevent counterfeit alcohol product crossing the customs boarder of the Eurasian Economic Union. The author paid special attention to regulation of alcohol product import by using excise stamps, methods of their obtaining and usage.